New international dictionary of Old Testament theology and exegesis ; vol. 4 (Grand Rapids, MI Zondervan, 1997)
Includes bibliographical references and index.
Keywords: Bible. O.T. -- dictionaries -- Hebrew; Bible. O.T. -- theology -- dictionaries; Bible. O.T. -- Criticism, interpretation, etc. -- dictionaries; Bible. O.T. -- theology -- dictionaries -- Hebrew; Bible. O.T. -- Criticism, interpretation, etc. -- dictionaries -- Hebrew